Duplex PCR assay for simultaneous detection of two aminoglycoside resistance genes in clinical samples of enterobacteriaceae - Theo, Chun Hao (2022)
Aminoglycosides include semi-synthetic and natural antibiotics isolated from Actinomycetes. They are well-known for their efficacy against the Enterobacteriaceae family. Nevertheless, the mass prescription of aminoglycosides in clinical settings has resulted in a significant rise in the number of aminoglycoside-resistant Enterobacteriaceae due to the presence of different resistance genes that synthesise aminoglycoside-modifying enzymes. In this study, a total of 60 clinical isolates of Enterobacteriaceae obtained from different hospitals in West Malaysia were subjected to eight antibiotics. Subsequently, the bacterial isolates were screened for the presence of ant(2’’)-Ia and aph(3’)-Ic genes simultaneously using duplex PCR. Twenty-three (38.33%) isolates of the 60 bacterial isolates were tested positive for ant(2’’)-Ia, 13 (21.67%) were tested positive for aph(3’)-Ic and only one (1.67%) bacterial isolate was tested positive for both ant(2’’)-Ic and aph(3’)-Ic genes. The prevalence of ant(2’’)-Ia and aph(3’)-Ic in Enterobacteriaceae was 40.00% and 23.33%, respectively. The ant(2’’)-Ia gene was more prevalent in Enterobacteriaceae as compared to the aph(3’)-Ic gene. Besides, E. coli and K. pneumoniae were found to host at least one aminoglycoside resistance gene. Statistical analysis determined that there were significant associations between the ant(2’’)-Ia gene with gentamicin, kanamycin, and imipenem resistance, and the aph(3’)-Ic gene with kanamycin resistance. However, the association between ant(2’’)-Ia gene with imipenem resistance may be caused by coincidence, in which the bacterial isolates hosting the ant(2’’)-Ia gene were carrying other imipenem resistance genes concurrently. This is because aminoglycoside resistance genes were proven to confer cross-resistance only within aminoglycosides, instead of other classes of antibiotics. Nonetheless, the age and gender of the patients have no statistically significant association with the resistance genes studied.